Highly water pressurized brown rice improves cognitive dysfunction in senescence-accelerated mouse prone 8 and reduces amyloid beta in the brain - Michiaki Okuda; Yuki Fujita; Takuya Katsube; Hiromasa Tabata; Katsumi Yoshino; Michio Hashimoto; Hachiro Sugimoto (BMC, 2018)
Abstract Background Alzheimer's disease (AD) is the most common form of dementia and the number of AD patients continues to increase worldwide. Components of the germ layer and bran of Brown rice (BR) help maintain good health and prevent AD. Because the germ layer and bran absorb little water and are very hard and difficult to cook, they are often removed during processing. To solve these problems, in this study, we tried to use a high-pressure (HP) technique. Methods We produced the highly water pressurized brown rice (HPBR) by pressurizing BR at 600 MPa, and then we fed it to an AD mouse model, senescence-accelerated mouse prone 8, to investigate the therapeutic effects of HPBR on cognitive dysfunction by Y-maze spatial memory test. Results HP treatment increased the water absorbency of BR without nutrient loss. HPBR ameliorated cognitive dysfunction and reduced the levels of amyloid-β, which is a major protein responsible for AD, in the brain. Conclusions These results suggest that HPBR is effective for preventing AD.